The case report of capillary leakage syndrome secondary to malignant hypertension. Issue 34 (August 2018) - Liu, Xuejiao; Wang, Guoqin; Sun, Lijun; Dong, Hongrui; Chen, Yipu; Cheng, Hong
Abstract: Introduction: Capillary leak syndrome (CLS) is characterized by hypoproteinemia, diffused pitting edema, noncardiogenic pulmonary edema, and hypotension. By far, there are no related reports of CLS secondary to malignant hypertension (MHT). A 33-year-old male was admitted to our hospital with the diagnosis of CLS on the background of MHT. Patient concerns: A 33-year-old male was admitted with a 6-day history of worsening dyspnea, chest distress, and diffused pitting edema accompanied by very high blood pressure (200/145 mm Hg). Diagnoses: The tests and examinations showed hypoalbuminemia (26.7 g/L), pulmonary edema, and normal heart function. However, the expected massive proteinuria was absent (1.5 g/24 h). After diuretic and other antihypertensive therapy, the blood pressure reduced gradually; meanwhile, the symptoms of dyspnea and chest distress were improved quickly, and edema in his legs was also reduced. It is surprising that there was no change of pulmonary edema signs on imaging scan, and hypoalbuminemia remained with only mild proteinuria. Thus, our provisional diagnosis of this patient was CLS secondary to MHT. Interventions and outcomes: We administered intravenous immunoglobulin, sulodexide, and renin-angiotensin system inhibitor to the patient for repairing vascular endothelium and improving the function of vascular endothelium. Before discharge, the patient's edema disappeared and the chest X-ray turned to normal. The level of serum albumin also increased to 35.1 g/L along with the overall improvement. Finally, the renal biopsy revealed malignant hypertensive glomerulosclerosis. All these clinical manifestations were consistent with CLS caused by MHT. Lessons: Up to now, there has been no case report of CLS caused by MHT. We should pay more attention to CLS induced by MHT, try to diagnose it as soon as possible, and give prompt treatment to CLS and primary disease.